2019
DOI: 10.14569/ijacsa.2019.0100963
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of IPv4 and IPv6 Networks with Different Modified Tunneling Techniques using OPNET

Abstract: Currently, all the devices are using Internet protocol version 4 (IPv4) to access the internet. IP addresses of the IPv4 are now depleted from IPv4 pool announced by IANA (Internet Assigned Number Authority) in February 2011. To solve this issue Internet protocol version 6 (IPv6) is launched. But the main problem is current devices can't support directly IPv6 that causes various compatibility issues. Many researchers have proposed various techniques, but still, their efficiency and performance is a big challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The IPv4 and IPv6 MPLS network were configured using the customer edge and supplier edge routers. It was found that ISATAP PE had minimum jitter and high throughput, whereas GRE CE had the lowest throughput and high jitter [53]. In 2020, M. A. Naagas et al used the Dual-stack, IPv6 only, IPv4, 6to4 tunnel broker mechanisms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The IPv4 and IPv6 MPLS network were configured using the customer edge and supplier edge routers. It was found that ISATAP PE had minimum jitter and high throughput, whereas GRE CE had the lowest throughput and high jitter [53]. In 2020, M. A. Naagas et al used the Dual-stack, IPv6 only, IPv4, 6to4 tunnel broker mechanisms.…”
Section: Literature Reviewmentioning
confidence: 99%